1950. Intentional Interprofessional Experiential Education in an HIV/Infectious Diseases Clinic - Ann Justo, Julie (Open Forum Infect Dis, 2019)
BACKGROUND: Experiential education opportunities, such as interprofessional practice, are currently limited in HIV care. This intentional interprofessional experiential education (IPEE) offering aimed to improve healthcare student attitudes, perceptions, and skills regarding interprofessional practice and HIV care. METHODS: An interprofessional team of faculty and clinicians designed a 2-week rotation, with each offering consisting of 6–9 students from 4 professions (medicine, nursing, pharmacy, social work). This intentional IPEE was delivered at a single ambulatory care infectious diseases clinic in Columbia, SC. It included time in clinic with providers from varying professions, didactic lectures, a peer health advocate session, and a team capstone project (i.e., simulated, then actual student team visit with an HIV-infected patient, plus note documentation/team presentation). Twelve offerings occurred from October 2016 to February 2019. Anonymous pre- and post-IPEE surveys were provided to each student at baseline and directly after to assess attitudes, perceptions, and skills regarding interprofessional practice and HIV care. Wilcoxon signed-rank tests were used to compare pre- vs. post-survey items. Multivariable logistic regression was used to evaluate predictors for interest in HIV as a specialty. RESULTS: Of 87 students, 84 (97%) completed both surveys (21 medicine, 25 nursing, 19 pharmacy, 19 social work). Attitudes toward healthcare teams significantly improved in 7/11 items (all P-values ≤ 0.019), teamwork perceptions improved in 5/8 items (P ≤ 0.017), and self-perceived team skills improved in all 6 items (P < 0.001). Students rated provider time in clinic as most valuable (mean 4.6, median 5 on 5-point Likert scale). Following the IPEE, the proportion of students interested in HIV care increased from 53% to 67% (P = 0.07). After adjusting for program year and profession, interest in HIV at baseline was a significant predictor of interest in HIV post-IPEE (aOR 8.2, 95% CI 2.6–25.5). CONCLUSION: Short-term, intentional IPEE can positively impact student attitudes, perceptions, and skills regarding interprofessional practice and HIV care. Clinical educators should incorporate intentional HIV IPEE in healthcare curricula. DISCLOSURES: All Authors: No reported Disclosures.